Gain-of-function mutations in the UNC-2/CaV2α channel lead to excitation-dominant synaptic transmission in Caenorhabditis elegans - Huang, Yung-Chi (2020)
Mutations in pre-synaptic voltage-gated calcium channels can lead to familial hemiplegic migraine type 1 (FHM1). While mammalian studies indicate that the migraine brain is hyperexcitable due to enhanced excitation or reduced inhibition, the molecular and cellular mechanisms underlying this excitatory/inhibitory (E/I) imbalance are poorly understood. We identified a gain-of-function (gf) mutation in the Caenorhabditis elegans CaV2 channel α1 subunit, UNC-2, which leads to increased calcium currents. unc-2(zf35gf) mutants exhibit hyperactivity and seizure-like motor behaviors. Expression of the unc-2 gene with FHM1 substitutions R192Q and S218L leads to hyperactivity similar to that of unc-2(zf35gf) mutants. unc-2(zf35gf) mutants display increased cholinergic and decreased GABAergic transmission. Moreover, increased cholinergic transmission in unc-2(zf35gf) mutants leads to an increase of cholinergic synapses and a TAX-6/calcineurin-dependent reduction of GABA synapses. Our studies reveal mechanisms through which CaV2 gain-of-function mutations disrupt excitation-inhibition balance in the nervous system.